Resource dynamics of the Indo-Pacific sailfish Istiophorus platypterus (Shaw, 1792) from the south-eastern Arabian Sea - Ganga, U.; Elayathu, M.N.K.; Prakasan, D.; Rajool Shanis, C. P.; Akhilesh, K. V.; Retheesh, T. B. (Indian Journal of Fisheries, 2012)
The average billfish catch from the Indian EEZ during 2002-2007 was 4561 t which increased to 7856 t during 2008-2010,and nearly 80% of this was caught from the Arabian Sea by drift gillnet cum longline units. In the Indian Ocean region,billfishes (marlins, swordfish and sailfish) are considered as data deficient resource in the IOTC database. The sailfishIstiophorus platypterus (Shaw, 1792) was the major component of the billfish catch at Cochin Fisheries Harbour from wherea fleet of gillnet cum longline units are regularly operated for oceanic fishes such as yellowfin tuna, seerfishes and pelagicsharks, besides billfishes. Length range of sailfish landed during 2005-2008 was 80-230 cm with inter-year variations in sizegroups contributing to the fishery. Length-weight relationship was estimated as 0.024 L 2.65 while growth parameters Lâˆž andK (annual) were estimated as 262 cm and 1.0 respectively. Diet preferences of fishes in the size range 180-227 cm indicatedpercent occurrence of fish as 81% followed by crabs (31%) and molluscs (25%). Trigger fishes (Balistes spp.) dominated thegut contents, followed by carangids like Selar spp. and Decapterus spp. Ova diameter of vitellogenic oocytes in ripe gonadwith hydrated eggs ranged from 200 to 1300 Î¼ with a major mode at 700 Î¼ and a minor mode at 1200 Î¼, indicating hydrated eggsare released in batches at probably close intervals. Absolute fecundity from a ripe stage ovary was estimated as 20,97,481 eggs(1750 eggs per g ovary weight) with hydrated eggs forming about 31% of the total eggs, giving a batch fecundity of about541 eggs per g ovary weight. Exploitation rate (E) indicated that although billfishes are considered as bycatch in the targetedfisheries for yellowfin tuna and pelagic sharks, the considerable number of fishing units operating for targeted tuna fishinghas resulted in heavy fishing pressure (E=>0.6) on the sailfish resource during certain years.